Hubungan asupan zat gizi makro dan aktivitas fisik terhadap status gizi mahasiswa Universitas Sriwijaya: Studi cross-sectional - Rahmiwati, Anita; Wulandari, Molas Maryunisa Salsabila; Sari, Indah Purnama; Etrawati, Fenny (Poltekkes Kemenkes Aceh, 2025)
Background: One of the fundamental aspects of nutritional problems arises due to the imbalance of food intake and body needs, which can lead to over or undernutrition. Research shows that 20,45% of university students are underweight and 4,54% are obese. College students are prone to disordered eating patterns, fast food consumption, and lack of physical activity, which can affect health and academic performance.Objective: To analyze the relationship between lunch macronutrient intake, physical activity, and nutritional status in Sriwijaya University students.Methods: This cross-sectional study involved 102 active students (2019–2023) who ate lunch at the faculty canteen, selected using purposive sampling considering class proportion. 24-hour food recall (two non-consecutive days) assessed nutrient intake, Body Mass Index (BMI) determined nutritional status, and the IPAQ questionnaire measured physical activity.Results: Significant relationships were found between energy intake (p = 0,000), carbohydrate intake (p = 0,000), protein intake (p = 0,001), fat intake (p = 0,006), and physical activity (p = 0,008) with nutritional status. Students with imbalanced nutrient intake and low physical activity were at higher risk of abnormal nutritional status.Conclusion: The study concludes that there is a significant relationship between lunchtime energy intake, carbohydrate intake, protein intake, fat intake, and physical activity with the nutritional status of Universitas Sriwijaya students. Students should maintain a balanced diet and increase physical activity to achieve optimal nutrition.